Movement Disorders in Autosomal Dominant Cerebellar Ataxias: A Systematic Review - Merello, Marcelo Jorge (2014)
Autosomal dominant cerebellar ataxias (ADCAs) are clinically heterogeneous disorders classified according to genetic subtype and collectively known as SCAs. In a few SCAs, movement disorders can be the most frequent extracerebellar sign. The aim of this article is to perform a systematic review of movement disorders frequency and characteristics in ADCAs. This work consisted of a structured search of electronic databases up to January 2013. Publications containing descriptions of ADCA clinical features written in several languages were selected initially based on title and abstract screening, followed by full-text reading of potentially relevant publications. Clinical findings and demographic data on genetically confirmed patients were extracted. Analysis of individual patient data from subjects with movement disorders was performed using the chi-square test and logistic regression. One thousand and sixty-six publications reviewing 12,151 patients from 30 different SCAs were analyzed. Individual data were available from 755 patients with at least one type of movement disorder during overall disease course. Of 422 patients in whom onset symptom data were available, one third referred a movement disorder as the initial symptom. During overall disease course, parkinsonism was common in many SCA subtypes, frequently described in the absence of ataxia and characterized as responding to dopaminergic medications. Motor complications developed occasionally in some patients as did nigrostriatal imaging alterations. Other frequent features were dystonia, chorea, and myoclonus. Rare conditions, such as akathisia, paroxysmal nonkinesigenic dyskinesia, or stiff person-like syndrome, were also reported. ADCA descriptions included a full range of movement disorders. Aside from postural or intention tremor, dopamine-responsive parkinsonism and dystonia were the most common.